Estudo de caso para ensino: deixa a vida me levar: o ônus da liderança laissez-faire no serviço público em detrimento da liderança contingencial - Ribeiro, Mônica de Fátima Vetromille (2015)
This paper analyzes the use of Case Study Teaching and its general rules, such as a pedagogical tool used in courses or courses that focus on the Government, as well as for use in cases of debates in organizational working groups to decision making. Presents the creation of a case and its pedagogical notes. This event, created by the author of this work, addresses on as an area manager of Human Resources of a Federal Institution of Higher Education deals with the management of their work processes and how it relates to employees, according to your style leadership.